ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BETERNAK SAPI DI DESA KOTO BENAI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Ekal Hendrayani; Dewi Febrina (Jurnal Peternakan, 2009)
The objectives of this research are : 1) to know the characteristics of cattle farmers in the village of Koto Benai -Kuantan Singingi, 2) to determine the factors that influence motivation in raising cattle of Koto Benai Village ~ Kuantan Singingi and 3) to know the level ofmotivation in raising cattle of Koto Benai Village -Kuantan Singingi. In this research, cattle farmers in the Koto ofBenai village who have their own cattle or get the sponsorship were used as respondents. Census method was use in this research by giving the queationnaires and direct interviews to the farmers, 25 cattle in the village of Koto Benai were as the samples. The characteristics of cattle farmers in the village of Koto Benai showed that the highly productive age (15 -45 years), 40% have complete the primary school is -do not finish high school, 64% never followed the non-Jorinal education, 60% had low family dependents «5 people), income was 60% (Rp.1.000.000 -2.000.000) and 60% had experience of trying to livestock is (2 -4 years). Motivation of the respondents as a whole is high with a score of 1.202. There is no correlation between motivation and factors that influence motivation (age, formal education, non-formal education, number offamily dependents, income, and experience in the cattle activities).